Philosophy-Based Da'wah in Digital Media in the Perspective of Discourse on Studying Philosophy Fahruddin Faiz on YouTube MJS Channel - Arinil Haq (International Journal of Sociology of Religion, 2025)
This study aims to analyze the construction of da'wah discourse in the "Ngaji Filsafat" program presented by Fahruddin Faiz on the YouTube channel MJS Channel. It focuses on how language, narrative, and communication strategies are used to build a reflective, inclusive, and contextual understanding of religion. Furthermore, this study aims to identify the paradigm shift in da'wah from dogmatic to dialogical, and from exclusive to inclusive within the context of digital da'wah. This study uses a qualitative approach with a descriptive-analytical approach and a critical discourse analysis (CDA) method that emphasizes three main dimensions: text, discursive practices, and social practices. Data were obtained through non-participatory observation of several episodes of "Ngaji Filsafat," documentation, and transcriptions of lectures relevant to the study's focus. The data were then analyzed using an interactive analysis model that encompasses data reduction, data presentation, and systematic and continuous conclusion drawing. The results indicate that the da'wah discourse constructed in this program is reflective, inclusive, and contextual. In the textual dimension, the use of communicative, argumentative, and narrative language enables the delivery of complex philosophical concepts to be more easily understood by the audience. In the discursive practical dimension, the presence of digital media opens up a space for participatory interaction between preachers and audiences, so that the meaning of da'wah is not singular but rather negotiated collectively. Meanwhile, in the social practical dimension, "Ngaji Filsafat" represents an effort to address the need of modern society for a rational, moderate, and open understanding of religion.